Analysis of Factors Affecting Workers' Blood Pressure - Sari, Ni Made Sekar; Mutiarahati, Ni Luh Ayu Citra; Gharbelasari, Dewa Ayu Anggi (Fakultas Kedokteran, 2026)
Hypertension is a non-communicable disease that often presents without clinical symptoms but significantly contributes to morbidity and mortality due to degenerative diseases. Workers, as a productive age group, play a strategic role in development; however, they often neglect their health due to job demands, limited time for routine health check-ups, and low awareness of healthy lifestyle behaviors. This study aims to analyze the factors influencing blood pressure among workers in Banjar Kertasari, Peguyangan Village, North Denpasar District. This study employed a quantitative design with an observational analytic approach and a cross-sectional method. The study involved 61 workers as subjects. Bivariate analysis was conducted using the chi-square test, while multivariate analysis was performed using logistic regression. The results showed that body mass index, medical history, physical activity, working hours, and blood glucose levels were significantly associated with workers’ blood pressure. Multivariate analysis indicated that physical activity was the most dominant factor influencing blood pressure. Workers with low levels of physical activity had a higher risk of elevated blood pressure. This study demonstrates that physical activity is the primary determinant of blood pressure among workers in Banjar Kertasari. Therefore, promotive and preventive efforts are needed through health education, increased routine physical activity, and regular blood pressure screening in the workplace to prevent hypertension.Keywords: Blood Pressure; Factors; Physical activity; Worker